1962
DOI: 10.1042/bj0840157
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of acetate into cephalosporin C

Abstract: Cephalosporin C, an antibiotic with structure (I) (Abraham & Newton, 1961; Hodgkin & Maslen, 1961), was first isolated from an impure preparation of the chemically related penicillin NJ [(D-4amino-4-carboxybutyl)penicillin] that had been obtained from the culture fluid of a Cephalosporium sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…sporium and Penicillium generate the a-aminoadipoyl moiety off,-lactam antibiotics via the lysine biosynthetic pathway (16,26).…”
mentioning
confidence: 99%
“…sporium and Penicillium generate the a-aminoadipoyl moiety off,-lactam antibiotics via the lysine biosynthetic pathway (16,26).…”
mentioning
confidence: 99%
“…This compound was cyclised in the C. aeremonium cell-free system and the resulting isopenicillin N was derivatised and examined by chemical ionisation mass spectrometry. It was found that all the oxygen labels were retained, ruling out intermediates such as (285) and (286). Similarly, when unlabelled LLD-tripeptide was cyclised in a reaction mixture containing H/70 and H2 18 0 no label was detected in the product, again ruling out (285) and (286) and also excluding such intermediates as enzyme bound thioesters, esters or amidines formed through any of the oxygen sites of the tripeptide.…”
Section: H2n~nh~h Sh H Coohmentioning
confidence: 94%
“…In order to establish whether intermediates such as (285) or (286) are involved in the cyclisation of LLD-tripeptide ADLINGTON et al (268) synthesised the tripeptide containing L-cx-aminoadipic acid labelled in all oxygens with 170rO. This compound was cyclised in the C. aeremonium cell-free system and the resulting isopenicillin N was derivatised and examined by chemical ionisation mass spectrometry.…”
Section: H2n~nh~h Sh H Coohmentioning
confidence: 99%
“…From the 1970s through the 1980s, knowledge accumulated concerning fermentation and biosynthesis of cephalosporin C. Of major importance was the (i) stimulation by DL -methionine via a regulatory mechanism unrelated to its ability to contribute the sulfur atom to the antibiotic [27] , (ii) use of acetate as precursor to the acetoxy group [28] , (iii) L -cysteine and L -valine [29] as precursors of the nucleus and (iv) L -α -aminoadipic acid as precursor of the D -α -aminoadipyl sidechain of cephalosporin C [30] . An important step forward was provided by Banko et al .…”
Section: The Coming Of the Cephalosporinsmentioning
confidence: 99%